2022
DOI: 10.5194/tc-2022-15
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Snow Avalanche Frequency Estimation (SAFE): 32 years of remote hazard monitoring in Afghanistan

Abstract: Abstract. Snow avalanches are the predominant hazards in winter in high elevation mountains. They cause damage to both humans and assets but cannot be accurately predicted. Until now, only local maps to estimate snow avalanche risk have been produced. Here we show how remote sensing can accurately inventory large avalanches every year at a basin scale using a 32-yr snow index derived from Landsat satellite archives. This Snow Avalanche Frequency Estimation (SAFE) built in an open-access Google Engine script ma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. A large number of human casualties have been reported in Switzerland, Austria, Italy, Türkiye, Afghanistan, Pakistan, Tajikistan and Canada [14,[24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. A large number of human casualties have been reported in Switzerland, Austria, Italy, Türkiye, Afghanistan, Pakistan, Tajikistan and Canada [14,[24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Bair et al [28] performed an analysis mainly related to the snow properties (with high potential to cause snow avalanches) in northwestern High Mountain Asia (regions in Afghanistan, Pakistan, and Tajikistan) by using the numerical snow cover modeling. The work of Caiserman et al [29] provided snow avalanche frequency estimation by using 32 years of remote sensing data in Afghanistan. The obtained results indicated that a total of 810,000 large avalanches occurred since 1990 within an area of 28,500 km 2 with a mean frequency of 0.88 avalanches/km 2 yr −1 , damaging villages and blocking roads and streams.…”
Section: Introductionmentioning
confidence: 99%